A “Hit and Run” Approach to Inducible Direct Reprogramming of Astrocytes to Neural Stem Cells - Poulou, Maria; Mandalos, Nikolaos P.; Karnavas, Theodoros; Saridaki, Marannia; McKay, Ronald D. G.; Remboutsika, Eumorphia (Frontiers in Physiology, 2016)
Temporal and spatial control of gene expression can be achieved using an inducible system as a fundamental tool for regulated transcription in basic, applied and eventually in clinical research. We describe a novel “hit and run” inducible direct reprogramming approach. In a single step, two days post-transfection, transiently transfected Sox2FLAG under the Leu3p-αIPM inducible control (iSox2) triggers the activation of endogenous Sox2, redirecting primary astrocytes into abundant distinct nestin-positive radial glia cells. This technique introduces a unique novel tool for safe, rapid and efficient reprogramming amendable to regenerative medicine.